The Effectiveness of Using a Monitoring Book for Parental Involvement in Early Childhood Pre-Literacy Development - Zia Zalzilah Mazfufah; Puji Yanti Fauziah; Elih Sudiapermana; Uyu Wahyudin (STKIP Singkawang, 2025)
This research is aimed to: (1) Examining the feasibility of parental involvement monitoring book in early childhood preliteracy’s development, (3) Measuring the effectiveness of the use of involvement monitoring book in early childhood preliteracy’s development. This research was using the experimental under ADDIE research and development model approach with quantitative methodh. The feasibility test was conducted using the Likert Scale. In the meantime, the effectiveness test was analyzed using the normality test, homogeneity test, t-test with a significance level of 0.05 and the N-Gain test. The results of the development research show: (1) monitoring books of parental involvement in early childhood development met the criteria of